2022
DOI: 10.1021/acs.iecr.2c02811
|View full text |Cite
|
Sign up to set email alerts
|

Toward Heat-Resistant and Transparent Poly(l-lactide) by Tailoring Crystallization with an Aliphatic Amide as a Nucleating Agent

Abstract: Poly(L-lactide) (PLLA) has been known as an important bioplastic with tremendous potential to replace some conventional fossil-based plastics; however, its commercial application still faces great challenges in terms of the implacable contradiction between high thermomechanical properties and exceptional optical transparency. Herein, we report a feasible and promising strategy to address this challenge by utilizing N,Nethylenebis(12-hydroxystearamide) (EBH) as an efficient nucleating agent (NA) to tailor the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…According to the Rayleigh theory, when the crystal size decreases to the nanometer level (i.e., much less than the wavelength of visible light, about 400–780 nm), the light scattering effect will become very weak, thereby ensuring high transmittance . For instance, Bai et al have tailored the crystallization process of PLA by adding a nucleating agent EBH, which can self-assemble to nanofibrous network structures, provide a large nucleation surface for crystal growth upon processing, and obtain good transparency . Wu et al have reported ternary PLA/poly­(methyl methacrylate) (PMMA)/α-cellulose blends with high light transmittance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Rayleigh theory, when the crystal size decreases to the nanometer level (i.e., much less than the wavelength of visible light, about 400–780 nm), the light scattering effect will become very weak, thereby ensuring high transmittance . For instance, Bai et al have tailored the crystallization process of PLA by adding a nucleating agent EBH, which can self-assemble to nanofibrous network structures, provide a large nucleation surface for crystal growth upon processing, and obtain good transparency . Wu et al have reported ternary PLA/poly­(methyl methacrylate) (PMMA)/α-cellulose blends with high light transmittance.…”
Section: Resultsmentioning
confidence: 99%
“…57 For instance, Bai et al have tailored the crystallization process of PLA by adding a nucleating agent EBH, which can self-assemble to nanofibrous network structures, provide a large nucleation surface for crystal growth upon processing, and obtain good transparency. 58 Wu et al have reported ternary PLA/poly(methyl methacrylate) (PMMA)/α-cellulose blends with high light transmittance. They believe that this is attributable to the introduction of αcellulose, which provides more crystallization sites and imparts smaller crystallites to PLA.…”
Section: Transparencymentioning
confidence: 99%
“…Promising results are achieved by the application of N,N'-ethylenebis(stearamide) (EBS) or N,N'-ethylenebis(12-hydroxystearamide) (EBHS) as nucleating agents 41,[195][196][197][198] . While both promote crystallization, an increase in the annealed samples' transparency and haze <10 % is reported 41,[195][196][197][198] .…”
Section: Modifying Pla With Additivesmentioning
confidence: 99%
“…Promising results are achieved by the application of N,N'-ethylenebis(stearamide) (EBS) or N,N'-ethylenebis(12-hydroxystearamide) (EBHS) as nucleating agents 41,[195][196][197][198] . While both promote crystallization, an increase in the annealed samples' transparency and haze <10 % is reported 41,[195][196][197][198] . Different derivates of N,N',N''-alkyl and N,N',N''-aryl-1,3,5benzenetricarboxylamides are also shown to act as a clarifiers due to the formation of smaller crystals [199][200][201][202][203][204] .…”
Section: Modifying Pla With Additivesmentioning
confidence: 99%
“…Another extensively studied category of organic NAs includes amides and hydrazides. These agents play a pivotal role in nucleation by facilitating the formation of helical structures within PLLA through intermolecular interactions between imino groups and PLLA’s carbonyl groups, resulting in a significantly enhanced promotion of crystallization. For instance, Cai et al synthesized and investigated aromatic hydrazide NAs, namely, N , N ′-bis (salicyloyl) p -phthalic acid dihydrazide. The hydrogen bonding between NA’s hydroxyl group and PLLA’s carbonyl group adsorbs the PLLA chains on its surface.…”
Section: Introductionmentioning
confidence: 99%